Subway Slugs. Tracking Displacement on the London Underground - Clarke, Ronald V. (The British journal of criminology, 1994)
Ticket vending machines, installed throughout the London Underground at the end of the 1980s, proved vulnerable to easily-made 50p slugs and had to be modified. Subsequent analysis of the distribution of slug use suggested that, while ordinary passengers and delinquents might have been responsible for the bulk of the problem, several groups of organized offenders had been systematically obtaining large sums of money from the machines at distinct clusters of stations. These offenders therefore seemed to be the likely culprits when {pound}1 slugs, which were much more difficult to make, began to appear soon after the 50p slugs were stopped. Because the same clusters of stations were not affected by the {pound}1 slugs, however, it was concluded that these slugs would have appeared anyway and were not simply the result of displacement. While the remedial measures introduced by the Underground were highly effective, the problem of slug use could have been anticipated at the design stage and might have been prevented by a greater initial investment in the machines